Non-pharmacologic hypertension management barriers and recommendations by hypertensive patients at Pentecost Hospital, Madina. - Evans Osei Appiah; Susana Boateng Agyekum; Amertil P Ninon; Cyndi Appiah (Public Library of Science (PLoS), 2022)
The number of hypertension cases keeps rising worldwide. Africa is not exempted from the prevalence of hypertension. The Sub-Saharan region over the years has been recording high numbers of hypertension cases due to low consciousness, poor management and lack of control of urbanization. However, it has been established that hypertension as a condition can be managed by controlling familiar risk factors such as alcohol consumption, tobacco use, physical inactivity and intake of an unhealthy diet. The researchers, therefore, intend to explore the non-pharmacologic hypertension management barriers and recommendations by hypertensive patients at Pentecost Hospital, Madina. The researchers employed the qualitative exploratory-descriptive design using a purposive sampling technique to select 20 participants between the ages of 35-65, who met the inclusion criteria. Using a semi-structured interview guide, participants were engaged in 30-60 minutes of face-to-face interviews. The demography of the participants revealed that 60% (12) were females, and 40% (8) were also males. Participants reported that they visit the clinic once a week with a budget of hundred Ghana Cedis to five hundred Ghana Cedis (100-500 GHS). Two main themes and 7 subthemes emerged from the study analysis. The barriers identified include financial constraints, difficulty adjusting to lifestyle changes, personal factors (laziness, forgetfulness, stress), lack of motivation, and busy work schedules and limited time. Recommendations were also made to overcome the barriers which include follow ups by health care professionals, and advice to hypertensive and non-hypertensive patients. In conclusion, the study found that adherence to non-pharmacologic management of hypertension is greatly influenced by one's finances, some personal factors and external influences. Hence, it is necessary address these factors and also to ensure effective follow-ups and reminders in order to improve adherence to the non-pharmacologic management of hypertension. Further studies can also be conducted to address other obstacles to non-pharmacologic hypertension management.